Model-Driven Engineering Tools and Languages for Cyber-Physical Systems–A Systematic Literature Review - Mustafa Abshir Mohamed (IEEE, 2021)
The development of Cyber-physical Systems (CPS) draws more interest from both researchers and industrial practitioners considering the opportunities they offer in almost all areas of industry. However, the engineering and management of CPS are challenging tasks due to their inherent heterogeneity and complexity characteristics. Regarding the development of CPS, there currently exists no standard methodology owing to the complexity of the domain. One of the key approaches to reduce the development complexity for CPS is Model-driven Engineering (MDE), which is frequently used in many industrial domains for software development to increase the level of platform abstraction. Nevertheless, it is always almost challenging, especially for the new researchers in this field, to determine the appropriate tools and languages to perform a particular MDE activity during CPS development. To the best of our knowledge, there is no guideline that demonstrates which language(s)/tool(s) to use for the various MDE techniques/phases for the development of CPS. This paper presents a Systematic Literature Review (SLR) study that focuses on identifying and classifying the recent research practices pertaining to CPS development by applying MDE approaches. With the objective of providing a general overview of the field, the study evaluates 140 research papers published during 2010–2018. Accordingly, a precise view of the various MDE tools and languages used in the development life-cycle of CPS, addressed MDE techniques/activities, and targeted CPS components is presented. We believe that the conducted study will guide researchers and practitioners to identify appropriate tools and languages according to the system requirements. It may also help in getting an overall understanding of the research trends for further research and development on the MDE of CPS.